Future Directions: A Model for Educational Partnerships in Australia - Beverly Moriarty (Journal of Research in Rural Education, 2003)
Educators are typically people who have much to offer their profession as well as the communities in which they work. This article analyzes the strategies used to develop a university postgraduate education program that involved input from stakeholders representing different educational systems in regional and rural Australia. The results indicate that professional goals can be achieved when people from regional or rural schooling systems and universities form strategic partnerships. The findings support the recommendation that empirically tested models of collaboration be used to guide the joint efforts of partners from different organizations. It is also recommended that partners formally evaluate their processes in order to contribute theoretically to existing models of collaboration and to other approaches less extensively researched. While this approach is likely to benefit people living in regional and rural parts of Australia, it could also be applied beyond the regional Australian context.